2019 IFFAS Award for Excellence Winner: Peri-Prosthetic Cysts and Alignment in Total Ankle Replacement: A 3-D, Weight Bearing Topographical Study. Issue 4 (16th October 2019) - Lintz, Francois; Mast, Jef; Mehdi, Nazim; Bernasconi, Alessio; de Cesar Netto, Cesar; Fernando, Celine; Buedts, Kristian
Category: Ankle, Ankle Arthritis Introduction/Purpose: Peri-prosthetic cysts (PPC) in Total Ankle Replacement (TAR) are a common failure cause but the mechanisms of their development remains unclear. One possible explanation could be hindfoot malalignment and subsequent unequal distribution of load inside the joint. However, how residual malalignment influences the evolution of PPC remains unclear. Computed tomography (CT) has demonstrated superiority on conventional radiography in the follow up of PPC. Weight Bearing CT (WBCT), by combining 3D imaging and weight bearing measurements seems a valid tool to investigate this further. The objective for this work was to study the effects of residual hindfoot deformity on the distribution of PPC in the coronal plane. We hypothesized that cysts would be found predominantly medially in varus configuration, and laterally in valgus configuration. Methods: Retrospective comparative study, ethics committee approved. Forty-eight cases of TAR were included, with relevant demographics. Inclusion criteria were cases of primary TAR with available WBCT imaging of their ankle as part of normal follow up. Exclusion criteria were subsequent implant revision or cyst grafting. In each case, the localization and size of PPC's were documented and their volume calculated by approximation of the closest ellipsoid. Hindfoot alignment was evaluated by the percentage Foot Ankle Offset (FAO) (foot-length normalized 3D ratio between the midline of the foot and the center of the ankle) using a WBCT dedicated semi-automatic software. The mean FAO value with 95%CI for the population was calculated. The difference in medial and lateral cyst volume defined by their position relative to the median axis in the coronal plane was compared in varus and valgus cases by a Mann-Whitney non-parametric test for unpaired samples. Results: Demographic distributions of the series were 32% female, mean age 65 (45-85) years. Mean FAO value was 0.12% (95%CI -1.09 to 1.33). Mean follow up was 43 months (6 to 239). The mean total cyst volume per case was 1190, 7 mm3. In varus cases (defined by FAO<-1.09%), the volume of medial cysts was greater than laterally by a mean 197 mm3, whereas in valgus cases (defined by FAO>1.33%), the volume of lateral cysts was greater than medially by a mean 332 mm3. The difference was statistically significant (p<0.05). There was a weak, significant positive correlation (r=0.25, p<0, 001) between FAO and total cyst volume and a moderate, significant correlation (r=0, 56, p<0, 001) between time to follow up and total cyst volume. Conclusion: Our hypothesis was confirmed. Periprosthetic cysts volume in this series of primary TAR was found to be relatively greater medially in postoperative varus configurations and vice-versa laterally in valgus. This confirms a possible correlation between the direction of residual hindfoot malalignment and the coronal localization of PPC in TAR, although this is certainly not the only pathophysiologic factor involved in PPC onset. Weightbearing CT may be helpful in Total Ankle Replacement follow up, in order to early detect PPC development and possibly to identify situations at risk of a more rapid evolution.